Embracing at arm's length: Ronald Coase's uneasy relationship with the Chicago School - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2019)
This paper takes up Coase's views on the Chicago school, as found in his published and, especially, unpublished writings, beginning already in the early 1960s, prior to his appointment at Chicago. These commentaries at once demonstrate a measure of kinship and significant differences of viewpoint, particularly as respects economic method. Pulling back the lens a bit further, the paper provides additional evidence for the heterogeneity of views on fundamental questions that existed even among ostensibly cornerstone members of the so-called "Chicago school." In doing so, it highlights the ambiguity surrounding the idea of a "Chicago school" and adds credence to claims that there was no "true" Chicago or, what amounts to the same thing, that there were many Chicagos.
Keywords: 330